Analisis Kepuasan Pengguna Terhadap Aplikasi Traveloka dengan Menerapkan Metode TAM - Nurhalima Nurhalima; Elvin Leander Hadisaputro (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
One of the e-commerce platforms used to fulfill people's travel needs is Traveloka, which is currently a popular platform with frequent visits by the public. Due to the large number of users who travel using the Traveloka application, a study was conducted to measure whether Traveloka application users are satisfied when using the application. This study aims to determine the effect of the Technology Acceptance Model (TAM) on user satisfaction with the Traveloka application. Data collection is done by spreading the distribution using google form. The results of the study prove that the relationship that occurs between the X variable (Perception of Ease of Use and Perception of Benefit) and Y variable (Perception of Interest Behavior) has a significant positive effect on the implementation of the customer satisfaction system on the Traveloka application in Penajam. Based on the analysis using SPSS, the reliability results obtained are 0.865.